Implementation of Groundwater Tax Services and Improvement in the Application of Electronic-Based Regional Revenue Management Information System (E-Simpatda) at the Langkat Regency Revenue Agency - Panjaitan, Deffi Erfian; Sinaga, Rudi Salam; Warjio, Warjio (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This research aims to determine the implementation of services and improvements in groundwater tax in the electronic-based regional revenue system (E-SIMPATDA) application at the Langkat Regency Regional Revenue Agency. This research was designed using a qualitative approach, the choice and theory used by the researcher in describing implementation was the theory of Van Meter and Van Horn in Sujianto (2008:35). The data analysis method was carried out qualitatively, the results of the research showed that (1) Langkat Regency Bapenda should be more active in providing education to the public, especially taxpayers regarding the function and use of taxes, (2) To provide more frequent outreach to the public, especially related taxpayers. rules and regulations regarding regional taxes, (3) To continue to increase human resources by continuing to provide opportunities for all employees who have them to take part in education or technical guidance especially in terms of inspections and bailiffs related to regional taxes, (4) must continue endeavor to improve information technology so that taxpayers can be served well.